2017
DOI: 10.3892/ol.2017.7059
|View full text |Cite
|
Sign up to set email alerts
|

TRIM37 promotes tumor cell proliferation and drug resistance in pediatric osteosarcoma

Abstract: Osteosarcoma (OS) is among the most frequently occurring bone tumors, particularly in children. Clinical treatment of OS is limited due to several factors including resistance to chemotherapy drugs and metastasis, and the underlying molecular mechanisms remain unclear. In the present study, tripartite motif containing 37 (TRIM37) expression levels were upregulated in tumor samples and associated with the development of drug resistance in OS. Furthermore, chemotherapy drug treatment (doxorubicin, cisplatin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Multiple studies reported that TRIM37 is overexpressed in cancers, including colorectal cancer, pediatric osteosarcoma, pancreatic cancer cells and hepatocellular carcinoma, however, the mechanism of TRIM37 upregulation in cancer remains unknown [33][34][35][36]. Interestingly, we found that TRIM37 exhibited a high ampli cation rate of 21.3% in ovarian cancer according to copy number variation analysis of TCGA datasets (https://www.cureline.com/the-cancer-genome-atlas.html), suggesting that the overexpression of TRIM37 in ovarian cancer is associated with genomic ampli cation.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies reported that TRIM37 is overexpressed in cancers, including colorectal cancer, pediatric osteosarcoma, pancreatic cancer cells and hepatocellular carcinoma, however, the mechanism of TRIM37 upregulation in cancer remains unknown [33][34][35][36]. Interestingly, we found that TRIM37 exhibited a high ampli cation rate of 21.3% in ovarian cancer according to copy number variation analysis of TCGA datasets (https://www.cureline.com/the-cancer-genome-atlas.html), suggesting that the overexpression of TRIM37 in ovarian cancer is associated with genomic ampli cation.…”
Section: Discussionmentioning
confidence: 99%
“…The overall survival rate of patients with OS is reported to be 60-80% (2)(3)(4). However, despite the advances in multiagent chemotherapy and surgical technique, the survival rate of patients with locally advanced or metastatic tumors at diagnosis is still very low (<20%) (5)(6)(7)(8)(9). Thus, there is urgent need to reveal detailed signal pathways involved in OS pathogenesis and the molecular mechanism of its metastasis, which may provide novel therapeutic targets for the clinical management of OS.…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of TRIM37 in vitro induced drug resistance, whereas TRIM37 knockdown restored chemosensitivity. The TRIM37-induced chemoresistance was found to be partially dependent on the activation of the Wnt/β-catenin signalling pathway [399]. These findings implicate the Wnt/β-catenin signalling pathway in chemoresistance in osteosarcoma and suggest that TRIM37 could be used as a target to supress activity of this pathway and increase drug sensitivity.…”
Section: Bone Pathways and Treatment Resistancementioning
confidence: 71%